2004
DOI: 10.1093/humrep/deh069
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of thrombophilia in women with repeated IVF failures

Abstract: These data suggest that inherited thrombophilia may play a role in the aetiology of repeated IVF failures, particularly in the subgroup with unexplained fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
117
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 14 publications
7
117
0
10
Order By: Relevance
“…On the basis that previous studies have linked pregnancy complications, including miscarriages, with thrombophilias, [32][33][34][35] mainly APS, we examined the number of pregnancies and miscarriages before and after each DVT episode, comparing thrombophilic with non-thrombophilic patients. Before DVTs, female patients in the thrombophilic group had more miscarriages than those in the control group and a greater number of gestational complications, as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis that previous studies have linked pregnancy complications, including miscarriages, with thrombophilias, [32][33][34][35] mainly APS, we examined the number of pregnancies and miscarriages before and after each DVT episode, comparing thrombophilic with non-thrombophilic patients. Before DVTs, female patients in the thrombophilic group had more miscarriages than those in the control group and a greater number of gestational complications, as reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature has conflicting findings in relation to the role of thrombophilia and its impact on repeat IVF failure. While some studies have suggested that repeat IVF failure may be associated with an increased incidence of thrombophilia [37][38][39][40][41] others have negated such an association [42][43][44]. In a recent systemic review and metaanalysis, pooled data from patients in 8 case control studies showed an overall 3-fold increased risk of ART failure in association with factor V Leiden; while in the 3 cohort studies there was no difference in outcome between those with and those without factor V Leiden mutation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies support the belief that thrombophilias lead to recurrent implantation failure [4][5][6][7]. Specifically, a small study of patients with at least three failed IVF cycles found that factor V Leiden mutations and prothrombin G20210A mutations were more prevalent in the recurrent implantation failure group versus the fertile control group Clinical Trial Number (ClinicalTrials.gov): NCT01223092…”
Section: Introductionmentioning
confidence: 96%
“…[4]. Another study found the presence of any of the following inherited thrombophilias: prothrombin G20210A, factor V Leiden, methylenetetrahydrofolate reductase (MTHFR), protein S deficiency, protein C deficiency, or antithrombin III deficiency, was more common in recurrent implantation failure patients, especially if they had unexplained infertility, when compared with fertile controls [5]. A similar study testing the same set of inherited thrombophilias showed combinations of two or more of these thrombophilic mutations that were found more often in the recurrent implantation failure group when compared with controls of patients succeeding with their first IVF attempt or fertile patients that achieved pregnancy by natural conception [6].…”
Section: Introductionmentioning
confidence: 99%